ALAT BANTU JALAN TUNANETRA MENGGUNAKAN SENSOR ULTRASONIK (STUDI KASUS : PUSAT LAYANAN DISABILITAS UNPAM) - Harits Chandra Dewata; Firman Pratama (CV. Multi Kreasi Media, 2024)
This study aims to develop a blind walker using an Arduino-based ultrasonic sensor. This tool is designed to assist the mobility of the blind in carrying out daily activities and increase awareness of obstacles or objects in front of them. This research uses the method of literature study, observation, and Rapid Application Development (RAD) in system development. This system uses an ultrasonic sensor to detect objects or obstacles that reflect ultrasonic waves, and is equipped with a buzzer that sounds as a warning sign. Mamdani's fuzzy logic method for controlling the intensity of the buzzer sound based on the distance detected by the ultrasonic sensor has the potential to increase accuracy in providing information about the presence of obstacles or obstacles for blind walker users.